The role of school culture and curriculum in improving Sport Education - Siska Aprelyani (Siber Nusantara Review, 2024)
Literature Review the role of school culture and curriculum in improving Sport Education is a scientific article with the aim to analyze whether school culture and curriculum in improving sport education. Metode Qualitative approach method with literature review method to explore and analyze the relationship between school culture, curriculum and sport education. The results of this article are: 1) school culture plays a role in improving Sport Education, 2) curriculum plays a role in improving Sport Education. Apart from these 2 exogenous variables that affect the endogenous variables of Sport Education, there are many other factors including the quality of Education, school facilities, interest in learning.